2008
DOI: 10.1093/humrep/den455
|View full text |Cite
|
Sign up to set email alerts
|

Information processing, attention and visual-motor function of adolescents born after in vitro fertilization compared with spontaneous conception

Abstract: Comparison of IVF adolescents and controls revealed no disturbances in information processing, attention and visual-motor function. In addition, these cognitive functions were not directly related to cardiometabolic outcome. Therefore, these results do not support the hypothesis that cognition is influenced by IVF conception or an altered programming of metabolic systems due to IVF, and indicate that cognitive abilities in IVF children, as measured by the tasks assessed, appear to develop normally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…Studies have shown that in ART there is a higher risk for preterm birth and low birth weight even after excluding twin births (Tarlatzis and Grimbizis , Wagenaar et al . , Schieve et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that in ART there is a higher risk for preterm birth and low birth weight even after excluding twin births (Tarlatzis and Grimbizis , Wagenaar et al . , Schieve et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Other influencing factors are preterm birth and low gestational birth weight. Studies have shown that in ART there is a higher risk for preterm birth and low birth weight even after excluding twin births (Tarlatzis and Grimbizis 1999, Wagenaar et al 2009, Schieve et al 2002. From the literature it is known that preterm birth and low birth weight increase a child's risk for developing a language impairment (Sansavini et al 2010, Wolke andMeyer 1999).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, lower scores on eye-hand coordination in ICSI children and worsened visual-motor competence in IVF adolescents were observed, although these scores were still within the normal range (Sutcliffe et al, 1999;Wagenaar et al, 2009b). Ponjaert-Kristoffersen et al (2004) additionally presented a trend indicating that ICSI children did worse on motor development than spontaneously conceived children when they were at the age of 5 years, though selection bias, educational level, age of the mother, and cultural differences might account for the differences that were found.…”
Section: Motor Developmentmentioning
confidence: 98%
“…However, the overwhelming majority of the studies on the neurodevelopment of children born at full term after ART consistently show that these children are in a comparable condition to NC children (Källén et al, 2005;Ponjaert-Kristoffersen et al, 2005;Leunens et al, 2006;Wagenaar et al, 2008;2009b;Hvidtjørn et al, 2009;Carson et al, 2010;Mains et al, 2010;Tsai et al, 2011). The follow-up studies have all focused on kids and adolescents through 18 years of age because of the short duration of ART's history.…”
Section: Neurological and Neurodevelopmental Outcomesmentioning
confidence: 99%